Nutrition and Athletic Performance - Ives, Stephen (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Exercise necessitates increased energy production to match the elevated demand of physical activity, the magnitude of which varies significantly by activity, sport, and/or athletic position. While long term nutritional habitus is known to impact exercise performance, short term or acute nutritional strategies may also prove beneficial, or detrimental, to athletic performance. Modifications to macro- or micro-nutrient intakes likely influence athletic capacity through the altered metabolic capacity, although cardiovascular, respiratory, or neurocognitive effects are not to be discounted as possibly being influenced by altering the nutritional approach. Similarly, dietary supplementation with factors such as probiotics or antioxidants, either acutely or chronically, is also a likely avenue in which to optimize athletic performance. Supplementation, or the timing of supplementation, diurnally or with activity, may help to bridge gaps between dietary intakes and needs, perhaps as a result of either an inadequate intake and/or high level of athletic demand via high intensity, frequency, volume, or a combination thereof. Altering nutritional strategy for athletic performance is a de facto approach employed by athletes, often occurring seemingly independent of knowledge or evidence for or against a particular strategy. Rigorous studies of nutritional manipulation, supplementation, or those exploring the temporal optimization of nutrition or supplementation are desperately needed in an ever-changing sports nutrition landscape with an increasingly larger audience.